Improving Learning Activities by Implementing Scientific Approach through Discovery Learning Model - Kuswati, Eni (Fakultas Ekonomi, Universitas Negeri Semarang, 2016)
This research aims to describe planning, implementation, observation and reflection. It evaluates and identifies the constraints and solutions at each cycle and to find out the learning outcomes achieved with scientific approach through the discovery learning model for 2nd grade students at Yunior High School 2 Kudus. It was a descriptive qualitative study. Findings show that the students’ activity is good enough on the first cycle and good on the second cycle. The average mean score of written test is on the first cycles B- and A- on the second cycle. If it is seen from minimum completeness criterion (KKM), there are 19 students with the percentage of acquisition by 55% on the 1st cycle and there are 32 students with the percentage of acquisition by 93% on the 2nd cycle. The observation results show that scientific approach give improvement of students’ activities on the first cycle and the second cycle. The results obtained from the use of scientific approach through the discovery learning model to improve the activity is good, but it needs to be observed continuously on students’ attitudes, skills and knowledge in school life.